TEACHERS SKILLS AND THEIR DEVELOPMENT FOR PROVISION OF QUALITY EDUCATION IN STEM EDUCATION PROGRAM - Vilkaste, Aivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
State higher education institutions constitute a new type of schools, in which the education process takes place in an integrated - school / university environment implementing Science, Technology, Engineering and Mathematics (STEM) education program and students are motivated and purposefully prepared for studies and career in the field of science and engineering. Teachers’ professional training is an important component for the successful implementation of education programs and for provision of the achievement of the objectives with the greatest likelihood of success. Teachers and students are constantly interacting and only highly qualified teachers, who have certain skills, can form and develop them in their students. Within the framework of the work there has been analysed teachers’ understanding of the aggregate of scientific principles of natural science and engineering and teachers’ collaboration and feedback provision skills and their impact on students, as well as there has been revealed the necessity to improve teachers' professional skills.